Pengembangan Objek Wisata Pantai Sunari di Kecamatan Bontosikuyu, Kabupaten Kepulauan Selayar - Pradana, Nur Najmi; Maddatuang, Maddatuang; Leo, Zakariah (Universitas Negeri Makassar, 2019)
ABSTRACTThis study aims to find out 1). To find out the inhibiting and supportingfactors in developing the Sunari Beach tourism object in Bontosikuyu District,Selayar Islands Regency. 2). To find out the development strategy of SunariBeach tourism object in Bontosikuyu District, Selayar Islands Regency. Thecollection of data using the method of observation, interviews and documentation. The sampling technique is accidental sampling. While for data analysis using descriptive analysis and SWOT analysis. Descriptive analysis is used to describe supporting and inhibiting factors in developing Sunari Beach tourism objects and SWOT analysis is used to find out strategies that can be done in the effort to develop Sunari Beach tourism object. SWOT analysis is also used to compare internal factors of strengths and weaknesses with external factors of opportunities and threats possessed by Sunari Beach attractions. The results of the study show that: the supporting factors that exist in the sunari beach attractions are the pristine, beautiful and comfortable natural scenery, the availability of vacant land, the support of the community, the easy level of accessibility, and good security conditions. The inhibiting factors are limited budget, promotion of tourism objects that have not been maximized, lack of professionals, no cooperation with the government, lack of awareness of visitors in maintaining cleanliness. The strategies that can be done include: 1) increasing tourism objects owned by sunari beach because it has interesting views to be used as a photo spot. 2) Utilizing vacant land to build facilities and infrastructure. 3) Improve the security of the sunari coast. ABSTRAKPenelitian ini bertujuan untuk mengetahui 1). Untuk mengetahui faktorpenghambat dan pendukung dalam upaya pengembangan objek wisata Pantai Sunari di Kecamatan Bontosikuyu Kabupaten Kepulauan Selayar. 2). Untuk mengetahui strategi pengembangan objek wisata Pantai Sunari di Kecamatan Bontosikuyu Kabupaten Kepulauan Selayar. Adapun pengumpulan data dengan menggunakan metode observasi, wawancara dan dokumentasi. Teknik pengambilan sampel yaitu accidental sampling. Sedangkan untuk analisis data menggunakan analisis deskriptif dan analisis SWOT. Analisis deskriptif digunakan untuk mendeskriipsikan faktor pendukung dan penghambat dalam upaya pengembangan objek wisata Pantai Sunari dan analisis SWOT digunakan untuk mengetahui strategi yang dapat dilakukan dalam upaya pengembangan objek wisata Pantai Sunari. Analisis SWOT juga digunakan untuk membandingkan antara faktor internal kekuatan dan kelemahan dengan faktor eksternal peluang dan ancaman yang dimiliki oleh objek wisata Pantai Sunari. Hasil penelitian menunjukkan bahwa : faktor pendukung yang ada pada objek wisata pantai sunari yaitu pemandangan alam yang masih asli, tersedianya lahan kosong, adanya dukungan dari masyarakat, tingkataksesibilitas yang mudah, dan kondisi keamanan yang baik. Adapun faktor penghambat yaitu keterbatasan anggaran, promosi objek wisata yang belum maksimal, kurangnya tenaga profesional, belum ada kerjasama dengan pemerintah, kurangnya kesadaran para pengunjung dalam menjaga kebersihan Adapun strategi yang dapat dilakukan diantaranya: 1)meningkatkan objek wisata yang dimiliki pantai sunari karena memiliki pemandangan yang menarik untuk dijadikan sebagai spot foto. 2) Memanfaatkan lahan yang kosong untuk membangun sarana dan prasarana yang. 3) Meningkatkan keamanan objek wisata pantai sunari.